PEMANFAATAN ARSIP REKAM MEDIS DALAM ANALISIS POLA TERAPI ANTIDIABETES PADA PASIEN JKN RAWAT JALAN DI RSUD KOTA MATARAM TAHUN 2025 - Muhammad Aditya Rachman (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
This study aims to analyze patterns of antidiabetic drug use by utilizing the medical records of National Health Insurance (JKN) outpatients at Mataram City General Hospital in 2023. Medical records, as dynamic archives, play a crucial role in providing authentic data for the evaluation of healthcare services. The research method employed was descriptive, using a retrospective approach based on the analysis of archival documents. Data were obtained from prescription records and medical records of patients with diabetes mellitus. The results indicate that the predominant therapy is a combination of oral antidiabetic drugs with metformin as the primary treatment. The use of medical record archives enables the systematic and accurate identification of treatment patterns. However, variations in medication use were still observed, indicating the need for more standardized record management to support clinical decision-making. This study confirms that proper management of medical records contributes to improving the quality of healthcare services.